Graph theory methods in analysing commuting networks of municipal electric transport - Kuz’kin, Olexiy (Eastern-European Journal of Enterprise Technologies, 2016)
The article presents an analysis of the development of route networks of municipal passenger electric transport in five large cities of Ukraine – Donetsk, Zaporizhia, Odesa, Lviv, and Kryvyi Rih. A comparative analysis of the topological characteristics of the networks and their impact on passenger traffic is based on the graph theory and the theory of complex networks. The surveyed route networks presented in the spaces of stops, connections and routes were processed with calculations of the average degrees of vertices, the value of the average shortest path, as well as the clustering and assortativity coefficients. Passenger traffic was determined on the basis of statistical data on the annual number of shuttle trips per one city resident. The research findings show that the electric transport networks in major cities of Ukraine occupy an intermediate position between regular and random graphs and contain features of the “tight world.” The method of correlation and regression analysis has revealed that passenger traffic on average increases linearly in route networks with higher values of the average shortest path and the assortativity coefficient in the space of connections, and linearly decreases in route networks with higher values of the average vertex degree and clustering coefficient in the space of routes. The study presents a substantive interpretation of the results that can be used to substantiate route networks’ development and assess the variation in passenger traffic.